(untitled) (Linguostylistic Studies, 2021)
The article elucidates the specific features of the linguistic and stylistic means actualization in the solemn speeches of the President of Poland. In the focus of the study are the stylistic tropes and figures of speech, considered as the means of the politician’s emotional speech expressiveness. The study highlights typical and individual author’s components of the linguo-stylistic organization of solemn speeches and analyzes the peculiarities of their functioning. In political discourse, ceremonial/solemn speeches traditionally adhere to the stylistic norms of the journalistic text. However, A. Duda’s public speeches differ from the established norms. They contain a lot of typical conversational constructions, which testify to his desire to deviate from the established stereotypes of communication in the political sphere. At the same time, the speaker always manifests a high level of communication skills and is generally in line with the official protocol. It has been revealed that the solemn texts of A. Duda have a clear structural organization as the tradition of the genre requires. However, there is a clear tendency to transform solemn speeches and increase the share of emotional and expressive means influence in them, which are often actualized in the text by means of stylistic tropes and figures. The study has revealed that linguistic and stylistic organization of the analyzed texts is distinguished by extensive use of the metaphorical constructions, lexical repetitions, high frequency of short sentences, parceling constructions, polysyndeton, and also rhetorical questions. The dominance of linguistic and stylistic means used to strengthen psychological influence on mass audiences is obvious. In the solemn speeches of the President of Poland, the study has identified a systematic verbalization of the dominant metaphorical patterns Poles - Family, Poles - Team, Poles - Unity, Poles - Nation, as well as the pronoun We indicating a community of people with traditions and culture, striving for changes. In most cases, the means of emotional expression in A. Duda’s speech is the repetition of the initial components of the sentence - anaphora, which performs an emotionally expressive, compositional, and accentuating function, focusing the audience’s attention on the basic provisions of the ceremonial speech. In addition to anaphora, the other dominant tools of the linguistic influence in the politician’s ceremonial speeches are antitheses and frequent quotations. In the texts of the analyzed speeches, we often fix not classical antitheses, built on the opposition of parallel constructions and antonyms, but emotional ones, which contain words and phrases, which in various contexts acquire either positive or negative evaluation. Emotional contrasts in A. Duda’s speeches are used to strengthen the psychological impact on the audience and reduce the negative or critical perception of the content. Repetitions of words, phrases, and, sporadically, sentences are due to the politician’s speech emotionality. At the same time, stylistically justified repetitions intensify the monologue, add weight, persuasiveness and expressiveness to public communication dicourse.